2016
DOI: 10.1038/srep27246
|View full text |Cite
|
Sign up to set email alerts
|

Daytime nap controls toddlers’ nighttime sleep

Abstract: Previous studies have demonstrated that afternoon naps can have a negative effect on subsequent nighttime sleep in children. These studies have mainly been based on sleep questionnaires completed by parents. To investigate the effect of napping on such aspects of sleep quality, we performed a study in which child activity and sleep levels were recorded using actigraphy. The parents were asked to attach actigraphy units to their child’s waist by an adjustable elastic belt and complete a sleep diary for 7 consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 17 publications
1
20
5
Order By: Relevance
“…These estimates are much lower than those in Western countries, such as Australia [23], Canada [22], the U.S. [50], or European countries [51]. The differences of night-time sleep duration between these Western studies and our current study may be partly due to discrepancies in daytime napping behaviour across cultures [52], and nap duration has been shown to negatively correlate with night-time sleep duration in young children [53].…”
Section: Discussioncontrasting
confidence: 67%
“…These estimates are much lower than those in Western countries, such as Australia [23], Canada [22], the U.S. [50], or European countries [51]. The differences of night-time sleep duration between these Western studies and our current study may be partly due to discrepancies in daytime napping behaviour across cultures [52], and nap duration has been shown to negatively correlate with night-time sleep duration in young children [53].…”
Section: Discussioncontrasting
confidence: 67%
“…Interestingly, daytime napping was a protective factor against shorter night-time sleep; toddlers who napped for 2 hours or more were at a decreased risk for shorter night-time sleep than their counterparts who napped for <2 hours. This is in contrast to findings reported by Akacem et al 49 Moreover, Nakagawa et al, 50 in a cross-sectional study among 50 children 1.5 years of age at a clinic in Tokyo, demonstrated that the longer the nap duration as denoted by "later nap-ending time", the later the toddlers' sleep onset and consequently the shorter the sleep duration at night. On the other hand, Komada et al 51 in a sample of 967 children aged 0-5 years found no significant differences in night sleep duration associated with napping duration in children younger than 2 years of age.…”
Section: Discussioncontrasting
confidence: 62%
“…For instance, one study showed that toddlers that habitually napped have later melatonin onset time, later bedtime, longer sleep‐onset latency and shorter night‐time sleep (Akacem et al., ). Another study showed that there was a negative correlation between nap duration, sleep onset time and night‐time sleep duration (Nakagawa et al., ). These results are in accordance with our findings and suggest that inappropriate amounts of daytime sleep can have a negative effect on subsequent night‐time sleep.…”
Section: Discussionmentioning
confidence: 99%